A hybrid approach to analyzing factors influencing international student retention in Turkish higher education: integrating fuzzy DEMATEL, machine learning, and statistical methods - Serra Usta Ergun (Journal of Fuzzy Extension and Applications)
Retention of international students poses a significant challenge for higher education institutions due to its social and economic consequences. This research investigates the connections between important variables, including intention to leave, integration commitment, educational commitment, student satisfaction, and challenges faced. A comprehensive model was utilized to examine how these factors influence retention, with a specific focus on the impact of demographic factors. Data was gathered from 2,736 international students enrolled in universities in Turkey and analyzed using IBM SPSS 26 and R software. The findings reveal that the intention to leave exhibits a negative correlation with integration commitment, educational commitment, and satisfaction, while showing a positive association with encountered difficulties. Furthermore, demographic factors such as language skills, quality of life, and family support play a significant role in influencing retention. The results of the hypothesis testing were further substantiated through the use of the fuzzy DEMATEL method, reinforcing the connections among the key variables. The outcomes indicate that the choice to leave is a complex, multifactorial issue, significantly influenced by both personal and institutional factors. As a result, it is essential to develop strategies that assist international students in their academic, cultural, and social environments to improve retention.